A Rebuttal to Perpetuating Victimization with Efforts to Reduce Human Trafficking: a Call to Action for Massage Therapist Protection - Kimmet, Deborah A. (International Journal of Therapeutic Massage & Bodywork, 2023)
This document is a rebuttal to Perpetuating Victimization with Efforts to Reduce Human Trafficking: a Call to Action for Massage Therapist Protection by Rosenow and Munk that appeared in the March issue. The paper is to be applauded for providing a massage therapist’s viewpoint on the issue of human trafficking guised as massage, and concisely summarizing the main impact on the profession. The solutions involved, however, are problematic, as is the underlying view that licensing practitioners and their businesses is de-signed to protect the massage therapist and trafficking victims. Finally, this commentary suggests a regulatory solution that should be implemented for any re-porting process to be successful.